(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The entrepreneurship provides them the satisfaction and assimilates a deep sense of accomplishment to create their own individuality in the society. In the present research paper, an attempt has been made to highlight the efforts taken and problem faced by the women entrepreneurs in retail business in Kerala. The objectives of the study are to find out socio-economic background of the women entrepreneurs, the study the steps taken by the women entrepreneurs in promoting retail business, to find out the major challenges faced by women entrepreneurs in retail business. The data collected with the help of primary and secondary source were analyzed by using tables, simple average and Weighted Average Garrett Ranking Technique. The empirical findings of the present survey are, most of the women entrepreneurs done their business on the shop. Discount is the main sales promotion devices followed by the respondents. This study finally concludes that rights efforts from all are required in the development of women entrepreneurs and their greater participation in the entrepreneurial activities.